Przedsiębiorstwo w nauczaniu społecznym Kościoła katolickiego - Stępniak, ks. Marek (Annales. Etyka w Życiu Gospodarczym, 2010)
Post-Vaticanum Secundum teaching of the Catholic Church emphasizes the role of different forms of social life for integral development of a human person. Communities, beginning with the natural one such as a family to the most complex ones determine quality of social life. Theological basis for the interest of various forms of social life are the truths about: social nature of a human being, common calling to salvation and the model of the Church as a community of people of God.The essential role of enterprises in contemporary economic life and their influence on lives of employees cause that social teaching of the Church has developed certain postulates relating to that specific form of social life. In the ethical reflection on an enterprise present in the Catholic social teaching, there are three clearly-cut planes: enterprises as communities of people, enterprises as a meeting place of capital and work, and important influence of contemporary (particularly international) enterprises on culture, on a family and economy, in a global dimension as well. Anthropological and deeply humanistic concept of an enterprise presented by the Church does not undermine its economic aspects, but puts a human person, a creator of social life in the center.